Crisis Management on the social network Facebook - Stránská, Adriana (2014)
The aim of the following thesis was to create a set of principles for crisis communication on Facebook. Presence in social media has become a standard part of any promotional mix. However, not every company fully recognizes the advantages and drawbacks of this tool. Once something goes wrong, the reputation of a company can be seriously endangered. The potential harm grows, when dealing with the issue is presented publicly. The thesis provides an analysis of how the emergence of social media changed the classical PR and a theoretical frame for a company's communication in case of negative publicity. In the analytical part two surveys were conducted, one within consumers to analyze their attitude towards making complaints on Facebook and the other one with social media experts by discussing their experience and opinions on this issue. Based on these findings, a set of 10 recommendations for crises on Facebook were formulated.